The Legitimacy of Traditional Village Levies and the Authorities of Traditional Villages in Bali Reviewed from the Accountability of Financial Management - Dewi, Ni Luh Sri Mahendra; Widiatedja, I Gusti Ngurah Parikesit; Yasa, Putu Gede Arya Sumerta (East Asian Journal of Multidisciplinary Research, 2024)
The theoretical issues surrounding the Balinese Traditional Village levy (stand) arise when compared to Article 23A of the 1945 Constitution of Indonesia, which mandates that taxes and levies for state needs must be regulated by law. However, Traditional Village levies, based on perarem and Article 18B paragraph (2), are fees rooted in local customary law. Deconstruction theory suggests that the legal text and context of these levies can be reconstructed to meet community needs, promoting justice and legitimizing Balinese Traditional Villages. The clarity and constitutionality of Bali Regional Regulation No. 4/2019 are crucial in ensuring that these levies are recognized as legitimate and not deemed extortion, as long as they are conducted in accordance with customary law.